Promoting Open Access at the Cyprus University of Technology: survey results - Giannoulakis, Stamatios; Zervas, Marios; Artemi, Petros (My University, 2012)
Today the Open Access movement gains more and more followers. The Library and Information Services at the Cyprus University of Technology has defined Open Access as one of its main strategies. Considering the current economic crisis, Open Access appears to be a solution to the reduction of funds at the academic institutions. The objective of this paper is to evaluate the perception and reaction of the academic community of the Cyprus University of Technology towards Open Access. The Library and Information Services conducted a survey in order to examine the familiarity of the academic community with Open Access and to define any difficulties that they find. The survey results showed that the academic community is generally aware of the Open Access movement, but a lot of effort and work has to be done in order to make the academic community to trust and use Open Access. The survey also showed that Ktisis, the institutional repository of the Cyprus University of Technology, is not being used effectively by the academics. It was proved that the deposits in Ktisis do not reach the desired level and the reason is that the academic community is not aware of its existence. Therefore the academic community has to be convinced to prefer Open Access publishers for the deposit of their academic publications instead of commercial publishers and to retain sufficient rights adopting the SPARC addendum. Also, to promote open access through “author pay model” like Biomed Central.
Keywords: Open access; Institutional repositories